Predictive Biomarkers for Immune Checkpoint Inhibitors in Advanced Non–Small Cell Lung Cancer: Current Status and Future Directions. Issue 6 (November 2020) - Bhalla, Sheena; Doroshow, Deborah Blythe; Hirsch, Fred R.
Abstract : Abstract: Immune checkpoint inhibitors (ICIs) have revolutionized the treatment paradigm for advanced non–small cell lung cancer (NSCLC). Although certain patients achieve significant, long-lasting responses from checkpoint blockade, the majority of patients with NSCLC do not and may be unnecessarily exposed to inadequate therapies and immune-related toxicities. Therefore, there is a critical need to identify biomarkers predictive of immunotherapy response. While tumor and immune cell expression of programmed death ligand-1 and, more recently, tumor mutational burden are used in clinical practice and may correlate with immunotherapy response in selected circumstances, neither consistently predicts an individual patient's likelihood of clinical benefit from ICI therapy. More recently, innovative approaches such as blood-based assays and combination biomarker strategies are under active investigation. This review will focus on the current role and challenges of programmed death ligand-1 and tumor mutational burden as predictive biomarkers for immunotherapy response in advanced NSCLC and explore promising novel biomarker strategies.